Trendelenburg Modifikasi Sebagai Upaya untuk Memperbaiki Status Hemodinamik pada Pasien Syok HemoragikGrade III : Studi Kasus - Ismi Asmaul Chair; Nita Fitria (Consilium Sanitatis: Journal of Health Science and Policy, 2023)
Objective: The purpose of conducting this case study was to identify the application of Trendelenburg modification to improve hemodynamic status in patients with grade III hemorrhagic shock. Methods: The method used in this study was descriptive analytic with a case study approach in grade III hemorrhagic shock patients with ineffective tissue perfusion nursing problems in the GICU B room of Dr. Hasan Sadikin Bandung. Data collection techniques include interviews, observations, physical examinations, observation flowcharts and medical records. Results: The results of this case study showed that after 2 days of modified Trendelenburg intervention, there was a significant increase in hemodynamic status. Conclusion: In conclusion, independent intervention by giving a modified Trendelenburg position can be an early intervention as an autotransfusion and improve hemodynamic status in patients with grade III hemorrhagic shock.